Melukai Orang Karena Membela Diri Dari Kejahatan Menurut Perspektif Hadits Bukhari Dan Pasal 49 KUHP - Dewi, Raenita Aulia; Arifin, Tajul (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
Crime is now rampant and causes fear and worry among the public. Perpetrators of crimes do not know the time and place to carry out their actions. Morning, afternoon, evening and in quiet or busy conditions, crime can occur. As humans, of course we have the instinct to defend ourselves when faced with a condition that puts us at risk. Various efforts are made to defend themselves against crimes, often when victims make resistance efforts to defend their rights or honor, causing the perpetrator to be injured or even killed by the victim. In fact, it is not uncommon for victims to become suspects because they accidentally and are forced to defend themselves, resulting in the loss of the life of the perpetrator of the crime. The purpose of this research is to find out what the perspective of the Bukhari Hadith and Article 49 of the Criminal Code is regarding injuring people because they are defending themselves from crime. This research uses library research methods. The data collection methods used are books, papers or articles, magazines, journals, web (internet) and so on.